Modelling automatic IoT home light system (SmartLi) by NODEMCU ESP8266 - Muhammad, Muttaqin; Nor Shazwanie; Najwa Raihana; Rohana, Abdul Karim (Springer Singapore, 2018)
Most people are always forgot to switch off the light when going out for holiday and left the light on as long as they are on holiday. This could lead to the waste of the electricity. If the lights turn off, dark condition and environment will attract and expose to the burglar target. Technology in network and communication system allows us to remotely control the light condi-tion either off or on in order to pretend the house is occupied. The aim of this project is to develop an automatic home light system that able to control remotely by using internet of thing (IoT) technology. Mobile application (SmartLi) for home light was developed and integrated with in-tensity and motion sensor. The porch lamp will light up when it’s dark and also it will become brighter when there is a motion detected in dark surrounding.